Strategi Pengembangan Pada Produk Inovasi Biskuneo (Studi Kasus: Tenant Badan Riset Inovasi Nasional) - Yuanto, Eka Novah; Raharja , Sapta; Aminah, Mimin (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2023)
Biskuneo is one of the innovative products resulting from research by the National Innovation Research Agency (BRIN) to find the right commercialization strategy based on market demand to support industry needs. The aims of this study were (1) to identify internal and external factors that influence the development strategy of Biskuneo innovation products and (2) to compile the application of the Biskuneo innovation product canvas business model to business development. The canvas business model method is used to map the condition of Biskuneo products, followed by a descriptive and quantitative analysis consisting of an internal factor evaluation matrix (IFE), an external factor evaluation matrix (EFE), an internal-external matrix (IE), a matrix of strengths, weaknesses, opportunities, and threats (SWOT). The IFE calculation result is 2.339 and the EFE calculation result is 2.580 which is mapped in the IE matrix in cell V, indicating that Biskuneo is in a position to grow and develop. Strategy determination in the SWOT matrix is ​​in quadrant I (SO strategy), namely the product has great opportunities and strengths so that it can take advantage of existing opportunities. The recommended strategy is an aggressive/progressive strategy.